The rat people : a journey through Beijing's forbidden underground - Saint-Paul, Patrick; Homel, David (Vancouver, BC, Canada : Arsenal Pulp Press, 2020)
"A shocking exploration of Beijing's notorious underground where over 1 million residents live: a sobering reminder of the human cost of capitalism. In a relatively short amount of time, China has become the second largest economy in the world and is soon poised to overtake the US. In 1978, when China introduced its economic reforms, its GDP was 214 billion USD; in 2019, it is estimated to increase to 14 trillion USD. But the country's rapid growth was achieved on the backs and shoulders of its workforce, many of whom were peasant farmers turned into the mingong, urban migrant workers, celebrated by Mao and credited with helping China achieve its economic miracle. Now, a million of them and their descendants live underground in Beijing under inhuman conditions, where there is no light or water and little sanitation. Author Patrick Saint-Paul spent two years living among the "rat people" (shuzu) of Beijing, in a network of deep tunnels and 20,000 former bomb shelters built during the Cold War. The mingong come to Beijing from all parts of the country, in search of jobs and a better life, but they are unable to afford their own homes on their meager salaries. For them, China's dream of prosperity for all is a bitter fallacy. In The Rat People, Saint-Paul brings the individual stories of the shizu to life, creating a shocking cautionary tale about the lengths to which people will go in search of a better life, and the human cost paid in service to the modern economy."--
Translation of: Le peuple des rats : dans les sous-sols interdits de la Chine.
Translated from the original French into English.
Description based on online resource; title from digital title page (viewed on May 20, 2020).
eBooks on EBSCOhost
Keywords: Working poor -- China -- Beijing -- Biography; Working class -- China -- Beijing -- Social conditions; Working class -- Housing -- China -- Beijing; Underground areas -- China -- Beijing; Rural-urban migration -- China -- Beijing; Migrant labor -- China -- Beijing -- Biography; Travailleurs pauvres -- Chine -- Pékin -- Biographies; Travailleurs -- Chine -- Pékin -- Conditions sociales; Travailleurs -- Logement -- Chine -- Pékin.; Zones souterraines -- Chine -- Pékin.; Exode rural -- Chine -- Pékin.; Travailleurs migrants -- Chine -- Pékin -- Biographies; HISTORY / Asia / China; Migrant labor; Rural-urban migration; Underground areas; Working class -- Housing; Working class -- Social conditions; Working poor; China -- Beijing; Biographies